Relational age and leader–member exchange: mediating role of perceived trust. Issue 4 (21st April 2020) - Gupta, Megha; Bhal, Kanika T.; Ansari, Mahfooz A.
Abstract : Purpose: Drawing on similarity-attraction hypothesis and generational gap literatures, this study aims to examine the impact of age difference in a leader–member dyad on leader–member exchange (LMX). The study hypothesized that relational age would impact the subordinates-reported LMX. However, given that leaders have structural power over subordinates and hence have mechanisms of interaction available to them, the age difference might not determine their perception of quality of LMX. The study also hypothesized that generation gap in values and beliefs leads to lack of trust, on the part of subordinates, which in turn might be the reason for poor quality of LMX. Design/methodology/approach: A total of 200 leader–member dyads from five organizations in the National Capital Region of India were used in this study. Data were collected via separate structured questionnaires for leaders and members, which comprised of standard scales of LMX and perceived trust, and demographics. Findings: Hypotheses received substantial support from the data with a few exceptions. Only the loyalty dimension of perceived trust mediates the relationship between relational age and member perception of LMX. Research limitations/implications: Results have implications for relational age and LMX interventions. However, the results are to be viewed in the light of members' perspective. While this is a common practice in LMX research, it would be interesting to explore leaders' trust and psychological reactions as well, for additional insights into leadership practice. Originality/value: Limited work has been done to explore the impact of relational age on LMX, that too mediated by trust. An attempt has been made in this study to do so via leader–member dyads.